2021
DOI: 10.5603/cj.a2019.0056
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of transesophageal echocardiography before cardioversion in atrial arrhythmias

Abstract: Background: Although many thromboembolism risk factors are well defined, formation of thrombus or dense spontaneous contrast (sludge) in the left atrium remains enigmatic and confounding. Exclusion of the thrombus is extremely important with respect to planned reversal of sinus rhythm. Data regarding the routine transesophagal echocardiography (TEE) before cardioversion are inconclusive. The authors focused on analyzing the usefulness of TEE before cardioversion by assessment of factors influencing the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…In the academic department, all patients have TEE performed routinely before direct current cardioversion of AF or catheter ablation for AF (pulmonary vein isolation) excluding those admitted for cardioversion for emergency indications, as described previously 2,6 . In the military hospital, preprocedural TEE was performed in case of any doubt regarding the efficacy of oral anticoagulation (OAC) or patient's compliance 7,8 . In both departments, TEE was conducted within 48 hours prior to the scheduled procedure (usually directly or a few hours before the procedure).…”
Section: Methodsmentioning
confidence: 99%
“…In the academic department, all patients have TEE performed routinely before direct current cardioversion of AF or catheter ablation for AF (pulmonary vein isolation) excluding those admitted for cardioversion for emergency indications, as described previously 2,6 . In the military hospital, preprocedural TEE was performed in case of any doubt regarding the efficacy of oral anticoagulation (OAC) or patient's compliance 7,8 . In both departments, TEE was conducted within 48 hours prior to the scheduled procedure (usually directly or a few hours before the procedure).…”
Section: Methodsmentioning
confidence: 99%
“…In patients with class I indications, the prevalence of LA thrombus was high both on VKA (13%) and on NOAC (7.6%), whereas in those with class IIa indications it was still high on VKA (11%), but much lower on NOAC (1.2%, p < 0.01). Thus, it may be suggested that patients with high thromboembolic risk (class I indications to OAC) should not be exempted from TEE before cardioversion or catheter ablation even after three weeks of OAC treatment [ 19 ]. In patients with class IIa indications to OAC, TEE before cardioversion might be reasonable in patients treated with VKA if no evidence for effective TTR is available.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that the incidence of left atrial appendage (LAA) thrombi or spontaneous echo contrast (SEC) is up to 29% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%